Vascular Protection of Hydrogen Sulfide on Cerebral Ischemia/Reperfusion Injury in Rats - Wen, Ji-Yue; Wang, Mei; Li, Ya-Nan; Jiang, Hui-Hui; Sun, Xuan-Jun; Chen, Zhi-Wu (Frontiers in Neurology, 2018)
This study was undertaken to demonstrate the vascular protection of exogenous and endogenous hydrogen Sulfide (H2S) on cerebral ischemia/reperfusion (I/R) injury. The effect of H2S on cerebrovascular dysfunction in middle cerebral artery (MCA) and neuronal damage were measured after cerebral I/R induced by transient middle cerebral artery occlusion (MCAO) in cystathionine c-lyase (CSE) knockdown and wild-type rats; the effect of sodium hydrosulfide (NaHS, donor of exogenous H2S ), L-cysteine (L-Cys, substrate of endogenous H2S) and endothelium cells on responses of isolated MCA derived from nonischemic rats were also evaluated to assess the underlying mechanism of H2S-mediate cerebral vasodilation. The results revealed that the contraction and dilation of MCA profoundly decreased after cerebral I/R. The vascular dysfunction became more grievous in CSE knockdown rats than that in wild-type rats. Interestingly, these vascular dysfunction were significantly alleviated by NaHS supplement. Moreover, both NaHS and L-cysteine could induce remarkable relaxation in the isolated MCA, which was obviously eliminated by co-application of potassium channel blockers ChTx and Apamin, or endothelial removal. By contrast, adding endothelium cells cultured in vitro together with ACh into luminal perfusate could mimic non-NO and non-PGI2 relaxation in endothelium-denuded MCA, once CSE was knocked down from endothelium cells, its effect on vasorelaxation was abolished. Furthermore, the indexes of neuronal injury were measured after cerebral I/R to confirm the neuroprotective of H2S, we found that neurological scores, cerebral infarction volume, brain water content, malondialdehyde content and serum lactate dehydrogenase activity (a marker of cellular membrane integrity) were significantly higher in CSE knockdown rats than those in normal control rats, not surprising, NaHS could alleviate the cerebral injury. These findings revealed that H2S has a protective effect on cerebral I/R injury and the protection could be due to its upregulate the endothelium-dependent contraction and dilation function of cerebral vessels via activating potassium channel.